Implementation of the Erga Omnes Principle on the Decision of the Constitutional Court (MK) concerning the Supreme Court's SE (MA) regarding Judicial Review - Ceprudin, Ceprudin (Walisongo Law Review (Walrev), 2021)
This study aims to analyse the decisions of the Constitutional Court (MK) and Circular Letters (SE) of the Supreme Court (MA) regarding Judicial Review (PK) in criminal cases. In March 2014, through decision No. 34/PUU-XI/2013, the Constitutional Court stated that in a criminal case, a PK may be conducted more than once. The verdict states that Article 268 paragraph (3) of Law no. 8 of 1981 concerning the Criminal Procedure Code (KUHAP) is contrary to the 1945 Constitution of the Republic of Indonesia. Interestingly, the Supreme Court issued SE No. 7 of 2014 which stipulates that PK is only allowed once. SEMA was signed on December 31, 2014, Chairman of the Supreme Court, Hatta Ali. The existence of the Constitutional Court and SEMA decisions has implications for the dualism of legal practice between only one time and maybe more than once in a PK application. Until now, the SEMA has not been revoked. The existence of the dualism of these rules seems to create uncertainty in the practice of PK law enforcement in Indonesia. Analysing the two legal products from two conflicting state institutions is very important to clarify the procedure for review. The review, which is also often called an extraordinary legal effort, is essential to maintain legal justice and safeguard the basic rights of citizens. In reviewing this fact, we will refer to the principle of Erga Omnes and its correlation with the protection of the basic rights of citizens. The principle of Erga Omnes (applies to everyone in the same case) must be heeded by all state institutions including the Supreme Court. In addition, regulation and its implementation must still pay attention to human rights. So this study uses the normative legal method. Based on the provisional facts presented, the authors hypothesise that SEMA should support the Constitutional Court's decision on PK as an implementation of the principle Erga Omnes and protect the basic rights of citizens. The principle of Erga Omnes and the framework for protecting basic human rights are two things that must be signed in the practice of review.[]Penelitian ini bertujuan untuk menganalisis putusan Mahkamah Konstitusi (MK) dan Surat Edaran (SE) Mahkamah Agung (MA) tentang Peninjauan Kembali (PK) dalam perkara pidana. Pada Maret 2014, melalui putusan No. 34/PUU-XI/2013, MK menyatakan bahwa perkara pidana, PK boleh lebih dari satu kali. Putusan itu menyatakan Pasal 268 ayat (3) Undang-Undang No. 8 Tahun 1981 tentang Hukum Acara Pidana (KUHAP) bertentangan dengan UUD NRI 1945. Menariknya, MA menerbitkan SE No. 7 Tahun 2014 yang menentukan bahwa PK hanya dibolehkan satu kali. SEMA ditandatangani pada 31 Desember 2014 Ketua MA, Hatta Ali. Adanya putusan MK dan SEMA itu berimplikasi pada dualisme praktik hukum antara hanya satu kali dan boleh lebih dari satu kali dalam permohonan PK. Hingga kini, SEMA tersebut belum dicabut. Adanya dualisme aturan tersebut seakan menimbulkan ketidakpastian praktik penegakkan hukum PK di Indonesia. Menganalisis dua produk hukum dari dua lembaga negara yang bertentangan itu sangat penting untuk menjernihkan tata cara peninjauan kembali. Peninjauan kembali yang juga kerap disebut upaya hukum luar biasa pada hakikatnya untuk menjaga keadilan hukum dan menjaga hak-hak dasar warga negara. Dalam mengkaji fakta ini, akan merujuk asas erga omnes dan korelasinya dengan perlindungan hak dasar warga negara. Asas erga omnes (berlaku bagi semua orang dalam perkara yang sama) harus diindahkan oleh semua lembaga negara termasuk MA. Selain itu, dalam sebuah aturan dan pelaksanaannya harus tetap memperhatikan hak asasi manusia. Sehingga kajian ini menggunakan metode hukum normatif. Atas fakta sementara yang tesaji, penulis berhipotesa bahwa SEMA seharusnya mendukung putusan MK tentang PK sebagai implementasi asas erga omnes dan melindungi hak-hak dasar warga negara. Asas erga omnes dan kerangka perlindungan hak dasar manusia merupakan dua hal yang harus menjadi rambu-rambu dalam praktik peninjauan kembali.